2020
DOI: 10.12659/msm.920725
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Sequencing, Connectivity Mapping, and Molecular Docking to Investigate Ligand-Protein Binding for Potential Drug Candidates for the Treatment of Wilms Tumor

Abstract: The funding was mainly used for data analysis and interpretation, and the costs incurred during the manuscript preparation Background:Wilms tumor, or nephroblastoma, is a malignant pediatric embryonal renal tumor that has a poor prognosis. This study aimed to use bioinformatics data, RNA-sequencing, connectivity mapping, molecular docking, and ligand-protein binding to identify potential targets for drug therapy in Wilms tumor. Material/Methods:Wilms tumor and non-tumor samples were obtained from high throughp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…CDK2 has been confirmed to be cell cycle regulators in many cancers. 33,34 The present study was consistent with these backgrounds, revealing that ABHD11-AS1 knockdown notably induced G1 arrest in pancreatic cancer cells through inactivating CDK2 and cyclin E1. Meanwhile, our finding indicated that ABHD11-AS1 regulated the tumorigenesis of pancreatic cancer via sponging miR-1231, which led to the dysfunction of miR-1231 according to competitive endogenous RNA network.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…CDK2 has been confirmed to be cell cycle regulators in many cancers. 33,34 The present study was consistent with these backgrounds, revealing that ABHD11-AS1 knockdown notably induced G1 arrest in pancreatic cancer cells through inactivating CDK2 and cyclin E1. Meanwhile, our finding indicated that ABHD11-AS1 regulated the tumorigenesis of pancreatic cancer via sponging miR-1231, which led to the dysfunction of miR-1231 according to competitive endogenous RNA network.…”
Section: Discussionsupporting
confidence: 89%
“…7,8 Recent studies have shown a close correlation between lncRNAs and cancer progression. 9,10 For example, knockdown of LINC00324 could suppress the progression of liver cancer through upregulation of PU box binding protein. 11 Additionally, some lncRNAs have been confirmed to play key roles in the progression of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, most cancers are caused by genetic mutation, so personal genomic and transcriptomic data analyses have been used to detect mutations in patients 1,2 . Furthermore, varies RNA‐seqs are used to predict the responses of drug treatment 3 …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Furthermore, varies RNA-seqs are used to predict the responses of drug treatment. 3 Detection of cancer at early stages can significantly impact survival of cancer patients. Recently, many studies have shown that the cancer survival rates are continually increasing, indicating that the early cancer diagnosis and treatment have been improved.…”
mentioning
confidence: 99%